CESifo World Economic Survey August 2014 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Michael Kleemann (CESifo World Economic Survey, 2014)
World Economic Climate: World economic climate brightens slightly - Economic Expectations: Economic expectations remain optimistic - Inflation: Persisting low inflation expectations - Currencies: US dollar expected to rise - Interest Rates: Interest rates expected to remain stable - Special Topic: Economic impact of the Ukraine crisis
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies